2020
DOI: 10.1177/0022042620912695
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Marijuana Legalization on the Trajectories of Hard Drug–Related Hospitalizations: A Growth Curve Analysis of the County-Level State Inpatient Database in Washington, 2009–2015

Abstract: Two antithetical arguments have raised controversies over the effect of recreational marijuana legalization on hard drug use. The gateway perspective posits that marijuana use diffuses hard drug use; however, recent studies argue that marijuana legalization displaces hard drug use. This study examines these conflicting arguments by investigating temporal patterns of hard drug–related hospitalizations (HDHs) before and after marijuana legalization. Using county-level State Inpatient Database data from Washingto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Recent studies, however, provide evidence that marijuana legalization laws actually displace harder drug use. A study conducted by Park et al (2020) considered these competing arguments and investigated temporal patterns of hard drug-related hospitalizations before and after marijuana legalization. County-level inpatient hospitalization data from Washington state from 2009 to 2015, along with additional federal data, were used for this analysis (Park et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies, however, provide evidence that marijuana legalization laws actually displace harder drug use. A study conducted by Park et al (2020) considered these competing arguments and investigated temporal patterns of hard drug-related hospitalizations before and after marijuana legalization. County-level inpatient hospitalization data from Washington state from 2009 to 2015, along with additional federal data, were used for this analysis (Park et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Park et al (2020) considered these competing arguments and investigated temporal patterns of hard drug-related hospitalizations before and after marijuana legalization. County-level inpatient hospitalization data from Washington state from 2009 to 2015, along with additional federal data, were used for this analysis (Park et al, 2020). Findings show support for the deterrent theory—increasing marijuana use seemed to deter individuals from partaking in harder drug use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there has been an important public concern about the consequences of marijuana legalization/marijuana use on other harder drug use, such as the use of heroin and cocaine 8 (Secades-Villa et al, 2015; Williams, 2020). Unfortunately, few studies have examined the relevance of marijuana legalization to the use of harder and more harmful substances (for examples, see Chu, 2015; Park et al, 2020). Given the connection between hard drugs and violence, further scholarly exploration on the relationship between marijuana legalization, marijuana use, and other harder drug use would help identify the mechanism of linkage between legalization and simple assault.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increases in emergency department attendances due to ingestion of marijuana products with higher than typical THC concentrations is probable [16]. Other studies have suggested the legalization of recreational marijuana acts as a "gateway" to other drug use [15,29]. Further evidence is necessary to better anticipate and prevent health risks associated with marijuana use [16].…”
Section: Introductionmentioning
confidence: 99%